Teachers practices on speaking assessment of Malay language in classroom assessment - Jamil, Halimah (Human Resource Management Academic Research Society, 2024)
The integrated system of classroom assessment in the teaching and learning process began in practice in 2012. The changes in education in the country that followed the previous examination-oriented system were considered to be inconsistent with the flow of education progress in the global context. This study attempts to explore teachers’ practices on speaking assessment of Malay language in classroom assessment. Qualitative research with case study design was conducted on six Malay language teachers. The six participants were selected from three secondary schools in one of the districts in Negeri Sembilan, Malaysia. The study data were collected through semi-structured interviews and document analysis. The main finding of the study showed that there were a number of participants not performing recording, follow-up, and reporting oral measurements. Participants are also unable to perform an oral evaluation deduction based on the performance standard in determining the level of mastery achieved by the student. This needs to be dealt with urgently, especially by the education policy so that the evaluation process can be carried out in accordance with the procedures specified in the Standard Curriculum and Assessment Documents (DSKP). This will affect students especially communication skills to face up to the challenges ahead. Even the quality of the teacher's teaching will be challenged. The Ministry of Education Malaysia must endeavour to ensure that the implementation of oral examination in schools is in line with the aspirations of Standard Curriculum for High Schools (KSSM).